2015
DOI: 10.1186/s12872-015-0003-7
|View full text |Cite
|
Sign up to set email alerts
|

A case report of eosinophilic myocarditis and a review of the relevant literature

Abstract: BackgroundEosinophilic myocarditis (EM) is a relatively rare condition that may result from parasitic infections and allergic disease. Antituberculosis drugs may lead to focal myocardial infiltration by eosinophils (eosinophilic myocarditis). Symptoms may be severe, and, lead to rapidly-fatal outcomes. Early diagnosis and high-dose corticosteroids are the cornerstone of treatment, and, may lead to restoration of cardiac function with full recovery.Case presentationWe report a case of eosinophilic myocarditis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 26 publications
0
24
1
Order By: Relevance
“…4 Although not well established in the pathophysiology of rejection, eosinophils are known to degranulate within myocardial tissue, releasing cationic proteins that mediate myocardial tissue damage and local inflammation in eosinophilic myocarditis. 16 However, other authors have failed to demonstrate a relationship between eosinophil count and the risk of rejection, 17 and at least one study has suggested that elevated eosinophil count may be protective. 18 Additionally, there are parallels in terms of clinical and histopathologic findings between our case and HES.…”
Section: Discussionmentioning
confidence: 99%
“…4 Although not well established in the pathophysiology of rejection, eosinophils are known to degranulate within myocardial tissue, releasing cationic proteins that mediate myocardial tissue damage and local inflammation in eosinophilic myocarditis. 16 However, other authors have failed to demonstrate a relationship between eosinophil count and the risk of rejection, 17 and at least one study has suggested that elevated eosinophil count may be protective. 18 Additionally, there are parallels in terms of clinical and histopathologic findings between our case and HES.…”
Section: Discussionmentioning
confidence: 99%
“…EM, a rare form of myocardial inflammation can be caused by various hypereosinohilic disorders, which include: -drug hypersensivity reactions (probably most common) [3] especially to antibiotics, antituberculotic drugs [7], anticonvulsants (carbamazepine) [8], anti-inflammatory, diuretics and inotropes (dobutamine) [9] and also antipsychotic clozapine [9,10] and toxins -parasitic infestations -toxocara canis [11,12], ascariasis [13], schistosomiasis, trichinosis, amoebiosis [6], toxoplasmosis [9] -idiopathic hypereosinophilic syndrome [9], -malignancies (T cell lymphoma, acute or chronic eosinophilic leukemia) [9,14] -paraneoplastic events (lung andenocarcinoma [15] or biliary tract cancers [9] -vasculitic and granulomatous disease (Churg -Strauss syndrome) [6,9] -tropical endomyocardial disease [6] -transplant rejections [6] In the case described above two possible aetiologies of EM might be suspected, which are Giardia lamblia infestation and Garcinia cambogia supplements admission prior to the hospitalization. The active agent of Garcinia cambodia is hydroxycitric acid, which plays a role in the inhibition of fatty acids synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] The decision was made to not add an immunosuppressive agent to their treatment regimen, as the offending drug agent had been removed, and it was theorized that it would likely not add any benefit. Patient improved clinically on corticosteroids and with removal of the offending drug agent.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Other case reports have documented high dose corticosteroids followed by a taper which have resulted in complete resolution of the disease. [5] Doses of steroids utilized in clinical care can be varied, but often courses of treatment are initiated with methylprednisolone regimen of 1 mg/kg/day, followed by a taper with varying durations. [4][5][6] Depending on the severity of the disease, high dose pulse therapy for up to three days is often included in the treatment regimen for those presenting in cardiogenic shock, later followed by starting 1 mg/kg/day regimen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation